Polifarmacy And The Compliance of Geriatric With Chronic Disease - Maya Arfania (Pharmed: Journal of Pharmaceutical Science and Medical Research, 2018)
The various geriatric’s health problem require complex treatment, which is by giving various drugs. Therefore, polifarmacy is a concequences of geriatric’s treatment. Polipharmacy is a serious problem in a health system. Besides can increase the health cost, also it can cause compliance problem. The purpose of this research is to see an overview the compliance level of geriatrics with chronic disease who receive a polipharmacy prescription. This is a descriptive research with cross sectional design. Data were obtained from outpatient prescriptions of geriatric’s with chronic disease in Yogyakarta’s hospital. From 100 prescriptions, there were 50 male and 50 female patients. In this research, most patients recieve 2 diagnoses (51%) and 48% polypharmacy prescription.  After the interview using MMAS 8 questionnare, there were 61% uncompliance geriatric’s patient , however the polypharmacy prescription isn’t significantly related to the patient’s compliance level. Keywords: Polipharmacy, geriatrics, chronic disease